PENGARUH INFLASI DAN KURS TERHADAP HARGA SAHAM DENGAN PROFITABILITAS SEBAGAI VARIABEL MEDIASI PADA PERUSAHAAN PERKEBUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Budiarti, Anindhyta; Friedel Syahl, Aulia (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
This research aims to determine the effect of Inflation and Exchange Rate on Stock Prices with Profitability as an mediating variable in plantation companies listed on the Indonesia Stock Exchange. The population of this study is all plantation companies on the Indonesia Stock Exchange for the 2018-2022 period with purposive sampling techniques so that a sample of 18 companies was obtained. The analysis used is path analysis through the Smart-PLS program with inner model analysis, hypothesis testing and mediation effect testing. The results of the study show that inflation has no effect on stock prices, inflation has a positive effect on profitability, exchange rates have a negative effect on stock prices, exchange rates do not affect profitability, profitability has a positive effect on stock prices. Meanwhile, profitability-mediated inflation has a positive effect on stock prices and profitability-mediated exchange rates negatively affect share prices in plantation companies listed on the Indonesia Stock Exchange.